Role of Environment as an Intervining factor in Conflict Management in Educational institutions Performance in Kenya - Iravo, Mike A. (Advances in Social Sciences Research Journal, 2017)
The purpose of the study was to examine the role of environment as an intervining factor in conflict management in educational institutions performance in Kenya with a view to solving conflicts being experienced in organizations and make them more effective, efficient and conducive for the development of human resources. Both qualitative and quantitative research was used. The research design used was descriptive survey. Data was collected using a semi-structured questionnaire. The target population was 140 public secondary school principals across Machakos County Government. Using stratified probability sampling based on different categories of schools and non- probability sampling, an optimum proportion of 30% was drawn from each category of the target population of schools to satisfy these requirements of optimality and representativeness. From each of the selected school, the principal that is the CEO was selected. Therefore, 43 principals were selected as the chief executive officers in-charge of management of the school organizations. Stepwise regression analysis was used. It showed zero significance between the role of environment in conflict management and performance of school organizations. These results were consistent with earlier empirical research on conflict management and organizational performance in organizations. In conclusion therefore, a two dimensional approach to conflict management, with concern for both high and low levels of being represented by the vertical axis, while maximum concern for both awareness of conflicts in an organization and approaches in handling conflicts is depicted along the horizontal axis. By pairing the two concerns and their value combinations we can identify three pure management roles, with each reflecting different systems of values. The fact that a chief executive prefers a given management role does not mean he or she will not use other management roles. Indeed, the model assumes that everyone uses each one of the management role at a time or another. However, the study proposes an environment role as being the intervening role under which the efficient and effective organizational performance is enhanced or achieved if practiced well.